Strategic leadership in liminal space: Framing exploration of digital opportunities at hierarchical interfaces - Putra, Fathiro H. R.; Pandza, Krsto; Khanagha, Saeed (Strategic Entrepreneurship Journal, 2024)
Research Summary We investigate how strategic leaders of an incumbent firm frame exploration of digital opportunities at the interfaces of organizational hierarchy. Digital technologies create an unbounded array of opportunities that may pose challenges to the strategic coherence of corporate entrepreneurship activity. Our analysis reveals that top management teams (TMTs) adopt a paradoxical framing of exploration, thereby creating a liminal space with unstable boundaries between exploration activities aligned with core resources (i.e., convergent) and those perceived as divergent. We show that middle managers (MMs) skillfully navigate this space by combining framing with substantive and symbolic actions to blur the boundaries of exploration. Drawing on our findings, we theorize the role of framing at the interfaces between the TMT and MMs in setting boundaries for exploration. Managerial Summary The process of digital transformation can be overwhelming for established companies as managers encounter a myriad of new opportunities. Our study of a large telecommunications company found that both senior and MMs play important roles in guiding the development of new digital businesses. Senior managers encourage creative thinking and promote exploring multiple innovation opportunities. However, they also set boundaries to prevent innovation activities from becoming too risky by venturing into very distant domains. This contradictive requirement creates a “gray zone” for MMs to imaginatively use their skills to navigate restrictions without compromising exploration of new opportunities. This approach involves both top‐down and bottom‐up communication between senior and MMs that helps avoid short‐sightedness and overspending when it comes to innovating with digital technologies.